2010
DOI: 10.1111/j.1471-0307.2010.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of volatile compounds in bovine milk heat treated by instant infusion pasteurisation and their correlation to sensory analysis

Abstract: Volatile compounds in skim milk and nonstandardised milk subjected to instant infusion pasteurisation at 80°C, 100°C and 120°C were compared with raw milk, high temperature short time pasteurised milk and milk pasteurised at 85°C ⁄ 30 s. The composition of volatile compounds differed between infusion pasteurisation treated samples and the reference pasteurisations. The sensory properties of skim milk subjected to instant infusion pasteurisation were described by negative attributes, such as cardboard sour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…However, 2‐nonanone had no flavor contribution because its OAV was less than 0.5 in raw milk (the threshold was 5 μg/kg in milk) (Vazquez‐Landaverde et al., ). The result of 2‐nonanone in raw milk was consistent with the previous studies (Hougaard et al., ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, 2‐nonanone had no flavor contribution because its OAV was less than 0.5 in raw milk (the threshold was 5 μg/kg in milk) (Vazquez‐Landaverde et al., ). The result of 2‐nonanone in raw milk was consistent with the previous studies (Hougaard et al., ).…”
Section: Resultssupporting
confidence: 92%
“…Compared with the previous studies, Hettinga, van Valenberg, and van Hooijdonk () identified seven compounds in raw milk using SPME–GC–MS (acetone, dimethyl sulfide, carbon disulfide, 2‐butanone, chloroform, pentanal, and hexanal), while six compounds (acetone, dimethyl sulfide, 2‐butanone, chloroform, pentanal, and hexanal) were identified using purge and trap–gas chromatography–mass spectrometry (PT–GC–MS). Hougaard, Vestergaard, Varming, Bredie, and Richard () found there were 12 kinds of flavor compounds using PT–GC–MS, while Contarini and Povolo () found nine kinds of flavor compounds using SPME–GC–MS in pasteurized milk. The types of flavor compounds found in this study differed from those with the previous reports, which probably reasoned from the factors of cow's lactation, environment, processing operation, and the identified methods.…”
Section: Resultsmentioning
confidence: 99%
“…The panellists (n = 29) blindfold received in a random order two samples of milk from L2 (one control and one sample subjected to one of the US combinations) that had to be compared with a known control sample. The panellists had to choose the sample that was the most similar to the control and to describe the difference between the control and experimental sample using one or more of the following attributes: stuffy, rubbery, cardboardy, burnt, sharp, sour, toffee, boiled milk, metallic, plastic, sweet and bitter (Chouliara et al, 2010;Hougaard, Vestergaard, Varming, Bredie, & Hipsen, 2011;Karatapanis, Badeka, Riganakos, Savvaidis, & Kontominas, 2006).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The contents of several ketones, aldehydes and sulphur compounds have been reported to increase during the processing and storage period [3,9,13,14], but comprehensive information is lacking on the aldehyde and ketone compounds and their changes during the production and storage of whole milk powder. Stapelfeldt et al [7] found that levels of free radicals and thiobarbituric acid reactive substances of low-heat whole milk powder were higher than the levels in high-heat and medium-heat milk powder and the sensory quality of low-heat powder dropped to an unacceptable level within 33 days of storage at 45 °C.…”
Section: Introductionmentioning
confidence: 99%